2011
DOI: 10.5194/bg-8-3423-2011
|View full text |Cite
|
Sign up to set email alerts
|

Inferring phytoplankton carbon and eco-physiological rates from diel cycles of spectral particulate beam-attenuation coefficient

Abstract: Abstract. The diurnal fluctuations in solar irradiance impose a fundamental frequency on ocean biogeochemistry. Observations of the ocean carbon cycle at these frequencies are rare, but could be considerably expanded by measuring and interpreting the inherent optical properties. A method is presented to analyze diel cycles in particulate beam-attenuation coefficient (c p ) measured at multiple wavelengths. The method is based on fitting observations with a size-structured population model coupled to an optical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 67 publications
3
22
1
Order By: Relevance
“…The depth-resolved time series of POC cp reveals a minimum at dawn and a maximum at dusk, reflecting losses at night, and growth + losses (A in Figure 2d) during the day. This finding is consistent with other studies that have observed diel cycles in c p or dissolved oxygen concentration within the euphotic zone from moorings (Stramska and Dickey, 1992) and floats (Claustre et al, 1999;Dall'Olmo et al, 2011).…”
Section: Phytoplankton Growth and Losssupporting
confidence: 93%
“…The depth-resolved time series of POC cp reveals a minimum at dawn and a maximum at dusk, reflecting losses at night, and growth + losses (A in Figure 2d) during the day. This finding is consistent with other studies that have observed diel cycles in c p or dissolved oxygen concentration within the euphotic zone from moorings (Stramska and Dickey, 1992) and floats (Claustre et al, 1999;Dall'Olmo et al, 2011).…”
Section: Phytoplankton Growth and Losssupporting
confidence: 93%
“…All data presented in this paper have been submitted to the Biological and Chemical Oceanography Data Management Office (BCO-DMO) and can be accessed from the "North Atlantic Bloom Experiment 2008" project page at https://www. bco-dmo.org/project/2098 (D'Asaro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fraction of Nanoplankton (cells 2-20 μm) Vidussi et al (2001) and Uitz et al (2006) attributed the diagnostic pigments 19′-hexanoyloxyfucoxanthin, 19′-butanoyloxyfucoxanthin (Goericke, 1995(Goericke, , 2002; B denotes data from the GeP&CO programme (Dandonneau et al, 2004); C denotes data from the BEAGLE cruise (Barlow et al, 2007); D denotes data from the BIOSOPE cruise (Bricaud, Babin, Claustre, Ras, & Tièche, 2010;Ras, Claustre, & Uitz, 2008); E denotes data from a Line-P cruise in the Subarctic Northeast Pacific (Werdell et al, 2003;Westberry, Dall'Olmo, Behrenfeld, & Moutin, 2010); F denotes data from a cruise in the Mediterranean Sea (Dall'Olmo et al, 2011;Werdell et al, 2003;Westberry et al, 2010); G denotes data from a cruise in the North Atlantic (Werdell et al, 2003;Westberry et al, 2010); H denotes data from a cruise in the Equatorial Pacific (Dall'Olmo, Westberry, Behrenfeld, Boss, & Slade, 2009;Werdell et al, 2003); I denotes data from the eastern Atlantic Ocean (Brotas et al, 2013); J denotes data from the Atlantic Meridional Transect cruises 1-22 (Aiken et al, 2009;Airs & Martinez-Vicente, 2014a, 2014b, 2014cBarlow et al, 2002;Gibb et al, 2000); K denotes data from the Agulhas ecosystem and Tanzania (Barlow, Kyewalyanga, Sessions, van den Berg, & Morris, 2008;Barlow et al, 2011); L denotes data from the Mozambique Channel (Barlow, Lamont, Morris, Sessions, & van den Berg, 2014); M denotes data gathered from various locations by the Bedford Institute of Oceanography (Devred et al, 2006;Sathyendranath et al, 2001); N denotes USJGOFS data in the Equatorial Pacific (Bidigare, 1994(Bidigare, , 1996; O denotes USJGOFS data from the Southern Ocean (RR_KIW) …”
Section: Fraction Of Picoplankton (Cells B 2 μM)mentioning
confidence: 99%